Prediksi Financial Distress Dengan Menggunakan Pendekatan Logistic Regression (Logit) - Azza Putrima Herita; Titin Hartini; Fernando Africano (FEB Universitas Sultan Ageng Tirtayasa, 2021)
Research conducted empirically tested the influence of financial factors on the possibility of financial distress. This research was conducted with quantitative methods using secondary data. The population of this research is listed companies on the Stock Exchange. Then the sample taken is based on purposive sampling with the criteria of a company that is not merged and has a complete financial report in accordance with research needs. This study uses logistic regression statistical tools because the dependent variable is a dummy variable, while the independent variable is a metric variable. The results showed that the leverage variable has a positive effect on the prediction of financial distress, then the profitability variable has a negative effect on the prediction of financial distress, the next variable is that the firm size variable has no influence on the prediction of financial distress.